Rethinking the Health Care Model through the reorientation of training - Carine Vendruscolo; Letícia De Lima Trindade; Marta Lenise do Prado; Maria Elisabeth Kleba
ABSTRACT Objective: to understand the contributions of the National Program of Reorientation of Professional Training in Health (Pró-Saúde) for the change in the model of care and training of health professionals. Methods: a case study with representatives of the teaching, care, management and social control, participants of the management units of the Pró-Saúde (Charitable institution for social and hospital assistance), in a municipality of the south of Brazil. Data collection took place through interviews and observations between October 2012 and February 2013. Results: the Program acts as a device for the transition of health care and training models, by promoting the problematization of daily work and the approximation between teaching and service. Emphasis is placed on the importance of the subjects' commitment and the different perspectives on the community. Conclusion: Pró-Saúde leaves visible marks in the process of qualifying students and professionals, as well as promoting collaborative action in the fields of management, care, teaching and social control in the SUS (Brazilian Unified Health System).